Design, fabrication and mechanical properties of a 3D re-entrant metastructure. (15th June 2023) - Yao, Yan; Park, Jeong Hun; Wang, Lizhen; Geng, Xuezhen; Liu, Jinglong; Xu, Peng; Huang, Huiwen; Hollister, Scott; Fan, Yubo
Abstract: A 3D re-entrant honeycomb structure was designed in a simple configuration by introducing a spatial angular design parameter. Mechanical responses under uniaxial compression of it at constant spatial angle ( α ) and different re-entrant angles ( θ ) were investigated both experimentally and theoretically. Designed lattice auxetic structures with high shape fidelity were fabricated using selective laser sintering (SLS) of PA 2200 powder. The produced samples exhibited negative, zero, and positive Poisson's ratios depending on a selected θ value, and their mechanical properties varied over a wide range. Bend- and buckling-dominated deformation mechanisms of the struts have been observed under compression. Additionally, the analytical models of re-entrant honeycomb structures effectively illustrated the quantitative relationships between their mechanical properties (Young's modulus ( E ) and Poisson's ratio) and the design parameter θ . The results presented in this study would provide a reference to the customized design of the porous auxetic structures with unique mechanical properties.